Harga Jual Dengan Metode Cost Plus Pricing Pendekatan Full Costing Pada Umkm Seblak Prasmanan Teh Lianti Kota Pekanbaru - Nur Fitriana; Erna Murniati; Zahwa Juwita; Mita Azira (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to evaluate the selling price using the cost-plus pricing method by applying the full costing approach to an UMKM (Micro, Small and Medium Enterprises) seblak stall called Teh Lianti. This UMKM specializes in culinary businesses, established in 2022, and located at Jl. Abat simpang Jl. Kuting No. 4, Kampung Melayu, Sukajadi District, Pekanbaru City, Riau. The data were obtained through direct interviews with the business owner, Teh Lianti, and applying quantitative methods. The data was then processed and adjusted using the cost-plus pricing method.The research results indicated that the total cost of goods produced based on Teh Lianti's UMKM was lower compared to the full costing method, resulting in a difference of Rp. 2,589,792 in the cost of goods produced, and a difference of Rp. 273 per portion.In the cost-plus pricing calculation, the researcher found that the resulting selling price was lower than the selling price set by the UMKM. This is because the UMKM did not calculate the selling price accurately and clearly based on the profit percentage. The researcher emphasizes the importance of conducting a detailed analysis of costs, competitors, and the market before setting a selling price that is appropriate to compete effectively in the market among other UMKM.